2017
DOI: 10.1007/s40121-017-0163-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Discontinuation, Adherence, and Real-World Effectiveness Among Patients Treated with Ledipasvir/Sofosbuvir in the United States

Abstract: IntroductionLedipasvir/sofosbuvir (LDV/SOF) for hepatitis C virus (HCV) treatment provides an oral interferon-free treatment regimen with high rates of sustained virologic response (SVR). This study assessed treatment discontinuation, factors associated with treatment completion, and real-world effectiveness.MethodsPatients with HCV treated with LDV/SOF between October 2014 and June 2015 and enrolled in a large US health plan were identified. Expected treatment duration was calculated based on IDSA/AASLD treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have demonstrated relatively high rates of SVR with DAAs in patients with recent or ongoing drug use in clinical trials and observational studies 35,36 . However, adherence to DAAs is variable 37 and may require intensive support strategies, especially in populations with transient living conditions 38,39 . For example DOT and close follow‐up visits have been recommended for persons not adequately engaged in care to help drive the likelihood of HCV cures after starting DAAs 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated relatively high rates of SVR with DAAs in patients with recent or ongoing drug use in clinical trials and observational studies 35,36 . However, adherence to DAAs is variable 37 and may require intensive support strategies, especially in populations with transient living conditions 38,39 . For example DOT and close follow‐up visits have been recommended for persons not adequately engaged in care to help drive the likelihood of HCV cures after starting DAAs 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of direct acting antiviral medications (DAAs) [ 2 ] for the treatment of HCV with fewer side effects [ 10 ], and the recommendation that all chronically infected HCV patients be treated [ 8 ], has had a significant impact [ 11 ]. These medications have sustained virologic response (SVR) rates as high as 97% in clinical trials, compared to approximately 50% with interferon-based regimens [ 12 ]. SVR is associated with decreased morbidity and mortality, and improved quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They remain highly effective among special populations, such as patients with chronic kidney disease (Ridruejo et al 2018), hemoglobinopathies (Origa et al 2017), HIV/HCV-coinfected individuals (Bhattacharya et al 2017; Hézode 2018), PWID (Grebely et al 2017(Grebely et al , 2018a, older individuals (Conti et al 2017), and those with advanced liver disease (Holzmann et al 2018). In real-life conditions, also, DAAs are highly effective (Cornberg et al 2017;Puenpatom et al 2017;Ji et al 2018). Overall, DAAs are significantly more effective, better tolerated, and easier to take than previous treatments.…”
Section: Hepatitis C Virus Epidemiologymentioning
confidence: 99%